UPAYA PENINGKATAN KOMPETENSI PROFESIONALISME GURU PENDIDIKAN DASAR DALAM PROSES PEMBELAJARAN - Okvi Ramayani (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The professional competence of basic education teachers plays an important role in the learning process in schools, and must always refer to actions that are rational and have certain specifications in carrying out their educational duties. Teachers as professional staff are required to have abilities and skills that are appropriate to the field they are working in, so that the process of growth and development of students' potential, which includes cognitive, affective, psychomotor and spiritual aspects, can run well and in accordance with the educational goals that have been set. This study uses a qualitative-descriptive approach with critical discourse analysis and literature review methods. Based on the results of the study, it can be concluded that efforts to increase teacher professional competence can be carried out through the following steps: first, efforts made by basic education teachers to increase their professional competence, including: attending teacher upgrading, training, national or international seminars, and teacher deliberations field of study, increasing knowledge through mass or electronic media, and professional advancement through independent study; and second, the efforts made by school principals to increase the professional competence of basic education teachers, including: empowering to increase the professionalism of basic education teachers through collaboration with advanced and developing basic education institutions, providing opportunities for basic education teachers to improve their profession, encouraging teacher involvement basic education in every school education activity (participatory), and increasing the knowledge of basic education teachers through deliberation, both among material teachers and as a whole.